Analysis of implemented mentoring program for undergraduate students in marketing - Gómez-Sánchez, David (Universidad Autónoma de Tamaulipas, 2011)
The present study aims to evaluate the tutoring program at the bachelor’s degree in marketing from the Media Unit Multidisciplinary Academic Area, San Luis Potosi, and identify the relationship between the dimensions of mentoring and student demographic characteristics. It is a cross-sectional descriptive and correlative tests that where applied through the Pearson bivariate correlation r and Spearman’s rho and t test for independent samples. The instrument assesses the following dimensions of mentoring, training, research training, teaching, training, academic counseling, socialization, academic sponsorship and psychosocial support. It was adapted from the instrument “selfdiagnostic functions and activities carried out by tutors in higher education in the context of society” (De la Cruz, 2010). Correlation was obtained between all dimensions of mentoring as well as a lack of appreciation of the dimensions that constitute it and found that only five of the eight dimensions are critical to the student deemed to have received tutoring in the program.